2013
DOI: 10.1620/tjem.229.97
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Correction Rate of Hyponatremia as an Independent Risk Factor for Neurological Complication Following Liver Transplantation

Abstract: Hyponatremia is prevalent before liver transplantation and generally corrected immediately after transplantation. However, the clinical significance of correction rate of hyponatremia is not well investigated. The prognostic impact of pre-transplant serum sodium concentrations and post-transplant correction rate of hyponatremia were assessed. A total of 512 patients who received orthotopic liver transplants were enrolled. The correction rate of hyponatremia (delta sodium, ΔNa) was calculated based on the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
17
1
1
Order By: Relevance
“…However, 49 of them were excluded because they did not included information about serum [Na + ] improvement (n = 37) or about mortality (n = 12) (see S2 file ). Four additional studies were excluded because they did not specifically address the association between mortality rate and serum [Na + ] improvement or normalization ( Table 2 ) [ 19 , 35 – 37 ]. Among the 15 selected studies, 7 studies evaluated the effect of hyponatremia improvement on overall mortality rate in subjects with heart failure, 2 in hospitalized series of subjects, one each including patients subjected to orthopic liver transplantation, admitted to an emergency room or to an intensive care unit, affected by lung cancer, myocardial infarction or pulmonary acute embolism ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, 49 of them were excluded because they did not included information about serum [Na + ] improvement (n = 37) or about mortality (n = 12) (see S2 file ). Four additional studies were excluded because they did not specifically address the association between mortality rate and serum [Na + ] improvement or normalization ( Table 2 ) [ 19 , 35 – 37 ]. Among the 15 selected studies, 7 studies evaluated the effect of hyponatremia improvement on overall mortality rate in subjects with heart failure, 2 in hospitalized series of subjects, one each including patients subjected to orthopic liver transplantation, admitted to an emergency room or to an intensive care unit, affected by lung cancer, myocardial infarction or pulmonary acute embolism ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Liver transplantation quickly restores hepatic function which, along with large volume of isotonic fluids given during surgery, may result in rapid correction of hyponatraemia with risk of ODS. Pre‐operative use of hypertonic saline may minimize this risk …”
Section: Resultsmentioning
confidence: 99%
“…Hypertonic sodium chloride has been used in the treatment of severe hyponatraemia in cirrhosis, but its efficacy is limited and is associated with increasing ascites and oedema; it is indicated only in cirrhotics who are very hyponatraemic and at only hours away from liver transplantation. The partial correction before transplantation is preferable to the rapid adjustment in the operating room to avoid ODS …”
Section: Resultsmentioning
confidence: 99%
“…14 Several studies have shown hyponatremia to be a poor prognostic indicator for cirrhotic patients receiving LTx. 9,[15][16][17][18] Yun et al 9 found that pre-operative hyponatremia is associated with an increased risk for post-operative ODS, along with prolonged stay in both ICU and hospital. On the other hand, few studies have focused on the rate of peri-operative SNa correction and its relationship with postoperative neurologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, few studies have focused on the rate of peri-operative SNa correction and its relationship with postoperative neurologic outcomes. [18][19][20] Yu et al 19 demonstrated a 3.5% incidence of ODS post-LTx that was associated with an increased rate of SNa correction.…”
Section: Introductionmentioning
confidence: 99%